The effect of the valence of sponsorship information on consumers' attitudes toward the sponsor brand. Issue 4 (15th August 2019) - Dick, Christopher
Abstract : Purpose: To date, research on sponsorship considers the effects of only positive or only negative sponsorship information on consumers' attitudes toward the sponsor brand. However, in practice, sometimes mixed information (positive and negative) is available that influences consumers' sponsor evaluations. To mirror the information situation of the real world, the purpose of this paper is to investigate how the valence of sponsorship information (only positive vs mixed vs only negative) and the strength of sponsorship information (weak vs strong) influence the consumers' attitudes toward the sponsor brand. Design/methodology/approach: This research uses an experimental research design ( n =210). Data were collected among students of a German university. Findings: The results reveal that when the strength of information was weak, attitudes in the mixed information condition were not significantly worse than in the only positive condition and significantly better than in the only negative condition. In addition, when the strength of information was strong, attitudes in the mixed information condition were significantly worse than in the only positive condition and significantly better than in the only negative condition. Practical implications: This study offers several practical recommendations regarding the sponsors' evaluation of their investments and the decision to maintain or exit the sponsorship of a controversial object. Originality/value: This study expands the research on the effects of available sponsorship information on consumers' sponsor evaluation. The present research highlights the effects of different types of sponsorship information on consumers' attitudes and considers the strength of information as a boundary condition of these effects.